2019
DOI: 10.1063/1.5091735
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced electro-mechanical coupling of TiN/Ce0.8Gd0.2O1.9 thin film electrostrictor

Abstract: Gadolium doped ceria, Gd:CeO2 (CGO), have recently been shown to possess an exceptional high electrostriction coefficient (Q), which is at the least three orders of magnitude larger than the best performing lead-based electrostrictors, e.g. Pb(Mn1/3Nb2/3)O3. Herein, we show that CGO thin films fabricated by a pulsed laser deposition method can be directly integrated onto the Si substrate by using TiN films of few nanometers as functional electrodes. The exceptional good coupling between TiN and Ce0.8Gd0.2O1.9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 45 publications
0
25
0
Order By: Relevance
“…[1][2][3] Furthermore, a recent discovery demonstrated that ceria thin films display an unconventional electromechanical strain at room temperature. [4][5][6][7] For example, the reported electrostriction coefficient (M e ) is around 6.5 Â 10 À18 (m V À1 ) 2 for [V O ] = 5%, i.e. 20 mol% Gd-doped ceria (GDC).…”
mentioning
confidence: 99%
“…[1][2][3] Furthermore, a recent discovery demonstrated that ceria thin films display an unconventional electromechanical strain at room temperature. [4][5][6][7] For example, the reported electrostriction coefficient (M e ) is around 6.5 Â 10 À18 (m V À1 ) 2 for [V O ] = 5%, i.e. 20 mol% Gd-doped ceria (GDC).…”
mentioning
confidence: 99%
“…We evaluated the electromechanical performances by measuring the longitudinal M 11 and the transverse M 12 electrostriction coefficients. We used the cantilever vibration method 23 on the samples with in-plane top electrodes (Fig. S1 †).…”
Section: Electrostriction Effect and Discussionmentioning
confidence: 99%
“…2,7,[17][18][19][20][21] At room temperature, doped ceria showed outstanding electromechanical properties due to local distortion in the vicinity of oxygen vacancies. 22 Studies carried out on Gddoped ceria (CGO) thin lms, [22][23][24][25][26] bulk 27,28 and membranes, [29][30][31] show an average electrostriction coefficient of M e z 6 Â 10 À18 (m 2 V À2 ), 22 which is comparable to that of state-of-the-art materials such as Pb(Mn 1/3 Nb 2/3 )O 3 (M e ¼ 2 Â 10 À18 m 2 V À2 ). 32 For classical electrostrictors, Newnham et al provided a relationship in which the logarithm of performances depends on (S/3), where S is the elastic compliance and 3 is the dielectric constant.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations